Analisis Penerapan Strategi Pemasaran Terhadap Kepuasan Pengunjung Pada Kolam Pemancingan Sumber Rezeki Di Tanjung Raja Kabupaten Ogan Ilir Sumatera Selatan - Nelly; Tutik Pebrianti (JURNAL EKOBIS Kajian Ekonomi dan Bisnis, 2024)
This research aims to determine and analyze marketing strategies in increasing visitor satisfaction at the Sumber Rejeki Fishing Pool in Tanjung Raja, Ogan Ilir Regency, South Sumatra as well as the impact of implementing the 7 P marketing mix which includes Products. Price, place, people, promotion, process and physical evidence. The method used in this research is descriptive qualitative and the data analysis technique uses an interactive qualitative analysis model. Data collection techniques were carried out using interviews, observation and documentation. The research results show that by implementing the 7P concept, this fishing pond has succeeded in optimizing the visitor experience and has had a significant impact, especially in increasing the number of visitors and repeat customers. It is hoped that the Sumber Rejeki Fishing Pool will continue to maintain and improve the implementation of the service marketing mix and pay special attention to the priorities expressed by visitors, such as expanding parking lots and increasing human resources. By continuing to maintain and improve the implementation of the service marketing mix, Sumber Rezeki Fishing Pool can strengthen its position as the main destination for fishing and recreation lovers in Tanjung Raja.